2010
DOI: 10.1053/j.gastro.2009.08.066
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cells Are Polarized Toward Cytotoxicity in Chronic Hepatitis C in an Interferon-Alfa–Dependent Manner

Abstract: Background and Aims: Patients with chronic hepatitis C virus (HCV) infection display great variability in disease activity and progression. While virus-specific adaptive immune responses have been extensively characterized and found to be impaired in chronic hepatitis C, the role of innate immune responses in disease activity and progression of chronic hepatitis C is not well understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

26
316
1
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 246 publications
(350 citation statements)
references
References 43 publications
26
316
1
5
Order By: Relevance
“…3 The exact role of NK cells in HCV infection, however, remains elusive, because current studies have yielded inconsistent results regarding phenotype and function of NK cells. [4][5][6][7][8][9][10][11][12] For example, surface expression and function of NKp46, a major activating receptor, is discussed controversially. 5,[7][8][9]33 These discrepancies might, in part, be explained by different characteristics of study cohorts and/or methodological issues.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…3 The exact role of NK cells in HCV infection, however, remains elusive, because current studies have yielded inconsistent results regarding phenotype and function of NK cells. [4][5][6][7][8][9][10][11][12] For example, surface expression and function of NKp46, a major activating receptor, is discussed controversially. 5,[7][8][9]33 These discrepancies might, in part, be explained by different characteristics of study cohorts and/or methodological issues.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] For example, surface expression and function of NKp46, a major activating receptor, is discussed controversially. 5,[7][8][9]33 These discrepancies might, in part, be explained by different characteristics of study cohorts and/or methodological issues. 28 Moreover, it is important to note that previous reports not only demonstrated varying expression of NKp46 in different NK-cell clones, but also suggested that density of NKp46 expression may correlate with cytolytic activity in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations